Sartorius muscle pierced by terminal branches of the lateral femoral cutaneous nerve: A case report with brief clinical commentaries - Robert Haładaj; Ivan Varga (Elsevier, 2024)
Introduction: Typically, the lateral femoral cutaneous nerve, also known as the lateral cutaneous nerve of the thigh (LCNT), runs under the inguinal ligament near the anterior superior iliac spine, runs anterior to the sartorius muscle and then divides into two terminal branches, i.e., anterior and posterior, which provide sensory innervation to the anterior and lateral thigh. This report describes an unusual anatomic variant in which terminal branches of the LCNT pierced the sartorius muscle. Case description: Dissection involved formalin-fixed right isolated lower limb. The procedure revealed anatomical variation of the LCNT. The nerve's division level into anterior and posterior branches was at the level of the inguinal ligament under the sartorius muscle. The posterior branch of the LCNT was directly adjacent to the anterior superior iliac spine. After a short course, this branch emerged from under the sartorius muscle lateral border 39 mm distally (in a straight line) to the inguinal ligament. The nerve's anterior branch pierced the sartorius muscle. It exited on the anterior surface of the muscle, 72 mm (in a straight line) from the inguinal ligament. The innervation territory of both branches was typical. We found no other anatomical variations of lumbar plexus branches. Conclusions: The LCNT terminal branches may show anatomic variations, which clinicians should consider during neurological assessments of nerve lesions. Deviations from the typical course of nerves should also be kept in mind when conducting surgical interventions.